Recent Advancement on Radical Urban Development in the Egyptian Desert - S. Abouelfadl; K. Ouda; A. Atia; N. Al-Amir; M. Ali; S. Mahmoud; H. Said; A. Ahmed (Modern Advances in Geography, Environment and Earth Sciences Vol. 3, 2021)
Gardens’ City is a new city in newly discovered area in the Egyptian western desert, which is rich to be developed. It lies in new Farafra Oasis. The site has different potential aspects for sustainable development; it has agricultural and industrial economic bases. The city center’s area is designed to be about 5% of the city’s area. The area of the industrial zone is about 22% of city area. This paper refers to the development of the city with a focus on the central and the industrial zones. The city center has the major managerial and commercial services. The industrial zone includes industrial areas as well as the major industrial education, training and managerial services. Renewable energy will be generated with different methods. This city will be the first step of development series opportunities in Egypt. Gardens’ City will have different sustainable options and the estimated yearly net profit for it would be 63-90 Million Egyptian pound (LE) and 394-535 Million LE yearly net profit for the whole new Farafra Oasis from olive, palm, and wheat only. This city will be the first step that opens great development opportunities in Egypt. Egypt has already adopted developing in the newly discovered areas and there are steps on the road.